2015
DOI: 10.1017/s1468109915000328
|View full text |Cite
|
Sign up to set email alerts
|

Developing Japanese Populism Research through Readings Of European Populist Radical Right Studies: Populism As An Ideological Concept, Classifications Of Politicians And Explanations For Political Success

Abstract: Former Prime Minister Koizumi's surprising victory within the Liberal Democratic Party (LDP) in 2001 and his subsequent popularity as prime minister led to increased interest in the study of populism in Japan. In addition toŌtake Hideo's prominent contributions, several others have also employed populism as a prism to study Japanese politics. Compared to the major debates on populism and particularly on the populist radical right (PRR) in Western Europe over the last two decades, however, the study of Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Prior research in Japan has indicated a disconnect between literature on populist leaders and parties and the actual voting behaviour of those voters classified as populists using existing survey scales (Hieda et al 2019). Japan's ruling party, the Liberal Democratic Party (LDP), is an "edge case" in terms of the adoption of populist rhetoric and strategies; while the LDP cannot reasonably be bracketed alongside overtly populist parties such as Hungary's FIDESZ or Germany's AfD, the party (especially under recent influential leaders, Junichiro Koizumi and Shinzo Abe) is argued to have adopted a number of elements of populist rhetoric, embracing what Yoshida (2019) describes as a "Japanese style of populism" (see also Lindgren 2015;Fahey et al 2021). This strategy has been argued to have been effective in limiting the appeal of potential populist challengers from outside the party (Warren 2019).…”
Section: Stan8mentioning
confidence: 99%
“…Prior research in Japan has indicated a disconnect between literature on populist leaders and parties and the actual voting behaviour of those voters classified as populists using existing survey scales (Hieda et al 2019). Japan's ruling party, the Liberal Democratic Party (LDP), is an "edge case" in terms of the adoption of populist rhetoric and strategies; while the LDP cannot reasonably be bracketed alongside overtly populist parties such as Hungary's FIDESZ or Germany's AfD, the party (especially under recent influential leaders, Junichiro Koizumi and Shinzo Abe) is argued to have adopted a number of elements of populist rhetoric, embracing what Yoshida (2019) describes as a "Japanese style of populism" (see also Lindgren 2015;Fahey et al 2021). This strategy has been argued to have been effective in limiting the appeal of potential populist challengers from outside the party (Warren 2019).…”
Section: Stan8mentioning
confidence: 99%
“…This circumstance is surprising, because although the number of publications that have been written (both by Japanese and non-Japanese authors) on the case of Japan is comparatively small, they mostly make a positive diagnosis regarding the existence of populism. Such a prominent author as Lindgren also came to this conclusion in his review article (Lindgren, 2015), and the majority of scientific articles that have appeared since Lindgren's publication have confirmed this finding. Nevertheless, if there is a populist current in Japanese politics that is hardly noticed internationally, the question arises why this is the case.…”
Section: Introductionmentioning
confidence: 70%
“…preferring to communicate directly to the public through television (Ohtake, 2003, 2006, 2009). Sharing this perspective, Lindgren (2015: 575) stresses Koizumi’s populistic characteristics: “In terms of his attacks on the politics-as-usual and on established political structures and actors in Japan, Koizumi’s style and rhetoric resembled what has been studied as populism elsewhere (in Latin America, in Northern America, and in Europe).”…”
Section: Is Populism Really (Now) Absent In Japan?mentioning
confidence: 99%